Relación entre la calidad de sueño y el síndrome metabólico en los trabajadores de la industria petrolera de Loreto, 2024 - Panduro del Castillo, Junior Fernando (2024)
Objective: To determine the relationship between sleep quality and metabolic syndrome in petroleum industry workers in Loreto during the year 2024. Methodology: A cross-sectional, observational, analytical, and quantitative study was conducted with a sample of 230 workers. This sample was calculated with a 95% confidence level and a 5% margin of error using Epidat V4.1 software. Sociodemographic and biochemical data were collected through access to medical records, and sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Results: It was found that 35.66% of the workers presented metabolic syndrome, with significant risk factors such as elevated triglycerides in 70.87% of cases andlowHDLcholesterollevels in 96.52%. Additionally, sleep quality was poor for the majority of participants, with 79.57% requiring some form of medical intervention. Bivariate analyses and a Poisson regression model were applied, showing that the prevalence of metabolic syndrome was 284% higher in workers with severe sleep disorders compared to those with adequate sleep (PR: 3.84; 95% CI: 2.14-6.91; p<0.001). Workers with sleep quality requiring medical intervention had a 110%increased likelihood of developing metabolic syndrome (PR: 2.10; 95%CI: 1.16-3.81; p=0.015). Conclusions: This study confirms a statistically significant relationship between sleep quality and metabolic syndrome among petroleum industry workers. The findings underscore the importance of implementing occupational health programs aimed at improving sleep quality to reduce the risk of metabolic diseases in this labor population